Some Inclusion Properties for Hohlov Operator to be in Comprehensive Subfamilies of Analytic functions (European Journal of Pure and Applied Mathematics, 2024)
In this paper, the subfamilies Cκ3 (κ1,κ2) and S∗ κ3 (κ1,κ2) investigated through the Hohlov operator. More specifically, a number of sufficient requirements are given in order for the aforementioned functions subfamilies. Moreover, our results will imply several corollaries.
Keywords: Analytic function; Geometric functions; Gaussian function; Hohlov operator